Implementation Of Quality Management In Maintaining Tapioca Flour Quality At Pd. Dermajaya Sumedang - Herawan, Amalia; Fadilah, Irvan Rahmat; Widiastuti, Sri Egi; Mardian, Tedy; Numan, Agung Khoerul; Gumilang, Elang Muhamad Husni; Ramdani, Iraz Lali (SINTESA, 2025)
Cassava is a primary source of carbohydrates in Indonesia, processed into tapioca flour with high economic value. Amidst intense producer competition, product quality is a crucial factor in maintaining competitiveness.This study aims to analyze the implementation of quality management at PD. Dermajaya Sumedang in sustaining the quality of tapioca flour production amidst market dynamics and industry competition. The research method employed was qualitative, focusing on quality management. Data were collected through interviews and direct observation. The result showed that PD. Dermajaya Sumedang implements quality management aspects including quality planning (selection of quality raw materials, prodution process planning, and operational standard implementation), quality improvement (defect identification, customer feedback), quality control (raw material reception, process supervision, final product testing). and quality assurance (raw material selection, process control, quality testing, emlpoyee training, monitoring and reporting). The implementation of these components has proven to be key in maintaining the quality of tapioca flour products. Nevertheless, the study also found that weather factors, especially in the drying process, significantly influence production volume and final product quality, potentially leading to defects, decreased selling prices, and increased return rates.This research provides insights into the quality management practices of small-scale tapioca flour industries in facing production and market challenges.